Dermatological Disorders Associated with Pregnancy - Szcześniak, Grzegorz; Kiełczewska, Aleksandra; Kiełczewska, Anna (Journal of Education, Health and Sport, 2025)
Introduction and purpose: Pregnancy is a remarkable and delicate period in a woman’s life, marked by significant physiological adaptations to accommodate the growing fetus. These changes affect every organ system, including the skin. The aim of this review paper is to raise awareness and assist clinicians in recognizing, diagnosing, and effectively managing these distinct skin conditions associated with pregnancy. Material and methods: An extensive examination of articles published in scientific journals was carried out through online research platforms PubMed and Google Scholar. We searched articles by entering keywords in appropriate configuration: “pregnancy dermatoses”, “pemphigoid gestationis”, “ polymorphic eruption of pregnancy”, “intrahepatic cholestasis of pregnancy”, “pustular psoriasis of pregnancy”, “atopic eruption of pregnancy”. Description of the state of knowledge: This diverse set of pregnancy-related skin conditions includes pemphigoid gestationis, polymorphic eruption of pregnancy, intrahepatic cholestasis of pregnancy, atopic eruption of pregnancy, and pustular psoriasis of pregnancy. Summary: Early diagnosis and treatment are crucial to mitigate maternal and fetal complications, and in some conditions, prevent fatalities. Improving clinicians’ in-depth understanding of these disease processes can enhance patient safety and quality of life during and after pregnancy.